AN ANALYSIS OF COMPARISON OF REGIONAL BUDGET MANAGEMENT IN PIDIE REGENCY BEFORE AND AFTER THE FORMATION OF THE NEW ADMINISTRATIVE REGION. - Nurmaya Sari; Abd. Jamal; Chenny Seftarita (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2019)
Abstract The purpose of this study was to analyze the comparison of budget management before and after the formation of the new administrative region in Pidie Regency. The data used for this study were the total value of Gross Regional Domestic Product (PDRB) toward constant price, total population and investment obtained from the Financial and Asset Management Board (BPKAD) and Central Statistics Agency of Pidie for the period 2002-2016. The analysis method used in this study was multiple linear regression with the ordinary least square (OLS) method and a dummy variable to distinguish the effect before and after the formation of new administrative regions. The results showed that the investment the BRDP affected locally-generated revenue (PAD), while the number of the population has an adverse effect on PAD. There was the negative difference on PAD before and after the formation of the new administrative region. On the contrary, the variables of BRDP, number of population, and the investment have a significant influence on PAD in Pidie Regency. The government must be more careful in budgeting how much it costs to realize all the income it receives so that it can be seen whether the revenue collection activities are efficient or not. This needs to be done because even though the regional government has succeeded in realizing revenue receipts according to the targets set, the success is less significant if it turns out that the costs incurred to realize the revenue target are greater than the realization of the income it receives.